Correlation Between DTI Findings and Volume of Corpus Callosum in Children with Autism - Temur, Hafize Otcu; YURTSEVER, İSMAİL; YURTSEVER, İSMAİL; YEŞİL, GÖZDE; YEŞİL, GÖZDE; SHARIFOV, RASUL; SHARIFOV, RASUL; Yilmaz, Fatih Temel; YILMAZ, TEMEL FATİH; DÜNDAR, TOLGA TURAN; DÜNDAR, TOLGA TURAN; ALKAN, ALPAY; et al. (My University, 2019)
Background: Autism Spectrum Disorder (ASD) is a complex developmental disorder in which neurological basis is largely unknown. The Corpus Callosum (CC) is the main commissure that connects the cerebral hemispheres. Previous evidence suggests the involvement of the CC in the pathophysiology of autism.